A survey on antibacterial effects of Iranian medicinal herbs on Staphylococcus aureus: Iranian Medicinal Herbs and Staphylococcus aureus - Baradaran, Masoumeh; Jalali, Amir (Iranian Journal of Pharmaceutical Sciences, 2023)
Due to the increasing prevalence of Staphylococcus aureus infections and resistance to long-term treatment with currently available antibiotics, S. aureus is well known. The search for new drugs, especially from natural sources, is underway. The use of plants for healing has been popular since ancient times. The benefits of herbs are minimal side effects, availability and usually low cost. Herbal research has become increasingly popular over the past few decades. Here, essential oils and various extracts (methanol, ethanol, ethyl acetate, ether, or aqueous extracts) from 31 genera of medicinal plants containing 83 species of S. aureus and its most common resistant strain, methicillin. The purpose is to evaluate the antibacterial activity of the review on the introduction of Methicillin-Resistant S. aureus (MRSA) as a potent therapeutic agent. This review describes species with known activity from which active compounds have not been isolated. Data from the present study supported, but limited, recommendations for routine use of Iranian herbs for the treatment of S. aureus infections. Iranian herbs have proven to be worthy of further clinical research to identify pure herbal compounds.